(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The in vivo effects of fruit pulp juice (MC-PJ) of Momordica charantia and its 1-butanol soluble part (MC-BP) and aqueous soluble part (MC-AP) on blood glucose of type 2 diabetic rats were studied. In vitro insulin secretion in response to MC-BP and MC-AP from whole perfused pancreas was measured. For elucidating the mechanism of insulinotropic action, the insulin secretory activity of MC-BP in the presence of 11 mM glucose, 50 μM verapamil (Ca++ channel blocker), 8 mM diazoxide (K+ ATP channel opener) and 10 mM theophylline (cAMP phosphodiesterase inhibitor) were studied. Serum glucose was measured by glucose oxidase-peroxidase method and rat insulin was assayed by specific ELISA. In the in vivo study, MC-BP significantly opposed the rise of serum glucose compared to control at 105 min (p<0.05). Although the MC-AP and MC-PJ lowered the serum glucose both at 60 and 105 min, these were not statistically significant. In the in vitro study, only MC-BP produced 22-fold increase in insulin secretion from the perfused pancreas at nonstimulatory glucose level, which was significant (basal vs. MC-BP, 0.071±0.009 vs. 1.563±0.150 ng/ml, p<0.001). The MC-BP also enhanced the insulin secretion from the glucose-stimulated pancreas (p<0.001). The MC-BP induced insulin secretion was not affected in presence of diazoxide and verapamil. The obtained results also showed that MC-BP enhanced the insulin secretory effect of theophylline (p<0.001). The findings indicate that MC-BP has stimulatory effects on physiological pathways of insulin secretion which may underlie its reported antidiabetic action. Dhaka Univ. J. Pharm. Sci. 19(2): 111-117, 2020 (December)